Development of Coconut Protein Concentrate-Xanthan Gum Conjugate by Wet-Dry Heating Method for Red Palm Oil Emulsification - Ramadhani, Anis Dwi; Setiowati, Arima Diah; Hidayat, Chusnul (agriTECH, 2024)
Protein-polysaccharide conjugation is commonly achieved by wet and dry heating methods. Therefore, this study aimed to produce red palm oil (RPO) emulsifiers by conjugating coconut protein concentrate (CPC) and xanthan gum (XG) through a combination of wet and dry heating method using a cabinet dryer. Several factors, including reaction time (3, 4, 5, 6, and 7 hours), pH (3, 5, 7, 9, and 11), and protein-polysaccharide ratio (1:3, 1:2, 1:1, 2:1, and 3:1) were evaluated for their effect on the Emulsion Activity Index (EAI) and Emulsion Stability Index (ESI). The ability of the obtaining conjugate to emulsify RPO was evaluated, and the results showed that CPC contained 67.40% protein. Reaction time, pH, and protein-XG ratio had a significant effect on EAI and ESI. Meanwhile, optimal conditions for the formation of the CPC-XG conjugate, based on EAI and ESI, were a reaction time of 5 hours, pH 9, and protein-polysaccharide ratio of 2:1. Fourier Transform Infrared (FTIR) analysis showed that the CPC-XG conjugate had a change in absorption at a wavelength number of around 1640 cm -1 , indicating the presence of a Maillard reaction product. Furthermore, the CPC-XG conjugate used in RPO emulsion has a characteristic EAI value of 23.74 m 2 /g, ESI of 271.32 minutes, a droplet size of 790 nm, and a zeta potential of -36.9 mV. These results suggest that the CPC-XG conjugate produced by the wet-dry heating method has the potential for producing stable RPO emulsions.